2014
DOI: 10.1159/000366334
|View full text |Cite
|
Sign up to set email alerts
|

Role of Continuous High Thoracic Epidural Anesthesia in Hippocampal Apoptosis after Global Cerebral Ischemia in Rats

Abstract: Background: Cervical sympathetic blockade has been found to reduce cerebral vascular resistance and improve focal cerebral ischemia/reperfusion injury. In this study, we tested the hypothesis that the sympathetic blockade of high thoracic epidural anesthesia (HTEA) would reduce hippocampal apoptosis after global cerebral ischemia (GCI) injury. Methods: Fifteen-minute global ischemia was established by 4-vessel occlusion in adult male Wistar rats. And 0.5% bupivacaine or 0.9% saline (20 μl//h) was infused conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Whereas, the neutrophils contribute significantly to I/R-mediated tissue and cellular damage [31,32] via toxic free radicals release during adhesion, migration and tissue infiltration. During this pathophysiological processes of I/R, the adhesion molecules including CD11b/CD18 on neutrophil [33,34] and ICAM-1 [34,35] on endothelium are the most important mediators.…”
Section: I/r Mediated Oxidative Stress In Skeletal Musclementioning
confidence: 99%
“…Whereas, the neutrophils contribute significantly to I/R-mediated tissue and cellular damage [31,32] via toxic free radicals release during adhesion, migration and tissue infiltration. During this pathophysiological processes of I/R, the adhesion molecules including CD11b/CD18 on neutrophil [33,34] and ICAM-1 [34,35] on endothelium are the most important mediators.…”
Section: I/r Mediated Oxidative Stress In Skeletal Musclementioning
confidence: 99%
“…Hypoxia inducible factor-1 (HIF-1) as an important endogenous signaling protein contributes to pathophysiologic changes of homeostasis under conditions of oxygen deprivation [5][6][7][8][9][10]. Accumulated subunit HIF-1α in the cellular nucleus and cytoplasm modulates the expression of several target genes that involve in neuroprotection, erythropoiesis, and apoptosis modulation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inadequate oxygen supply appears in the brain regions during global ischemia, which is associated with ischemiaevoked pathophysiologic changes [13,14]. Recent studies have demonstrated that HIF-1α is expressed in the brain tissues including hippocampus, indicating that HIF-1α is engaged in hippocampal apoptosis after induction of global ischemia [6,[13][14][15]. Using a rat model of asphyxial cardiac arrest (CA), our recent study has further demonstrated that HIF-1α is increased in the hippocampus of rats with CA [16].…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of evidence has demonstrated that IL-1β and TNF-α play a role mainly via p38 MAPK, ERK and JNK signaling transduction pathways, but IL-6 plays a role via JAK-STAT pathways [27][28][29]. After activation of those signaling pathways, gene transcription occurs [30][31][32]. What different mechanisms by which those signaling transduction pathways are responsible for regulating expression of GAT-1 and GAT-3 via PIC receptors needs to be determined.…”
Section: Discussionmentioning
confidence: 99%